The environmental impact of Swedish adolescents’ diets - Anna Karin Lindroos; Anna Winkvist; Elin Röös; Elinor Hallström (Environmental Research: Food Systems)
Adolescence is a critical life stage characterised by rapid development and openness to change. Habits formed during adolescence tend to progress into adulthood, making adolescents a key target group for interventions promoting long-term sustainable dietary patterns. This study quantified the environmental impact of Swedish adolescents’ diets using eight indicators: carbon footprint, cropland use, new nitrogen (N) and new phosphorous (P) inputs, blue water use, pesticides use, biodiversity impact, and ammonia emissions. The national dietary survey Riksmaten Adolescents 2016–17 ( n = 3099 adolescents, aged 11–12; 14–15; 17–18 years) was used in the analyses. Impacts were compared with per capita global planetary boundaries for the food system for six indicators and described by sex and age-group for all indicators. The carbon footprint, N and P inputs, and biodiversity impacts substantially exceeded planetary boundaries, even in the quartiles with the lowest impacts. Cropland use was slightly above, whereas blue water remained below. All environmental indicators were higher in males than in females, with the highest impacts observed in the oldest males. When standardizing for energy intake, indicators with the highest contribution from red meat and dairy (carbon footprint, cropland use, N input, ammonia emissions) and P input remained higher in males, whereas those dominated by plant-based foods and discretionary foods (blue water, pesticides) were higher in females. Biodiversity impact did not differ by sex. In the oldest female group beverages contributed to almost 40% of the biodiversity impact. This study shows notable differences in environmental impact by age and sex. The results highlight the importance of including multiple environmental indicators to capture diverse impacts of food consumption. Furthermore, they inform policies aiming at promoting sustainable dietary patterns.